Correction: Preisegger et al. Visualizing Oral Infection Dynamics of Beauveria bassiana in the Gut of Tribolium castaneum. J. Fungi 2025, 11, 101 - Lautaro Preisegger; Juan Cruz Flecha; Fiorella Ghilini; Daysi Espin-Sánchez; Eduardo Prieto; Héctor Oberti; Eduardo Abreo; Carla Huarte-Bonnet; Nicolás Pedrini; Maria Constanza Mannino (Journal of Fungi, 2025)
In the original article [...]